Differential effect of pharmacological autonomic blockade on some electrophysiological properties of the human ventricle and atrium. Issue 1 (January 1994) - Shimizu, W.; Tsuchioka, Y.; Karakawa, S.; Nagata, K.; Mukai, J.; Yamagata, T.; Matsuura, H.; Kajiyama, G.; Matsuura, Y.
Abstract : OBJECTIVE--This study investigated the dominance of each limb of the autonomic nervous system and tested sympathetic-vagal interactions in the human ventricle and atrium after administration of propranolol and atropine. PATIENTS AND METHODS--The 90% monophasic action potential duration (MAPD90) and the effective refractory period (ERP) at the right ventricular apex (RV) and the right lateral atrium (RA) were measured in 14 patients. The MAPD90 was measured during constant RV and RA pacing (cycle length 600 ms) and the ERP was measured at a driven cycle length of 600 ms. Electrophysiological variables were measured during a control period, after propranolol (0.15 mg/kg loading dose followed by 0.1 mg/min infusion), and after autonomic blockade (atropine 0.04 mg/kg). RESULTS--Both RV MAPD90 and RV ERP increased after propranolol (RV MAPD90 from 268 (26) ms to 275 (26) ms, p < 0.005; RV ERP from 252 (25) ms to 258 (26) ms, p < 0.0005) and then decreased to below the control values after autonomic blockade (RV MAPD90 256 (24) ms; RV ERP 239 (25) ms, p < 0.0005 v propranolol, p < 0.0005 v control). In contrast, both RA MAPD90 and RA ERP increased after propranolol (RA MAPD90 from 242 (19) ms to 260 (19) ms; RA ERP from 216 (21) ms to 230 (18) ms, p < 0.0005), and then increased slightly more after autonomic blockade (RA MAPD90 265 (16) ms, p = 0.09; RA ERP 235 (16) ms, p = 0.07), thus remaining above control values (p < 0.0005). CONCLUSIONS--The results indicate (a) that in the human ventricle vagal stimulation and sympathetic beta stimulation are antagonistic and that direct vagal stimulation predominates over beta stimulation, with sympathetic-vagal interaction being minimal and (b) that in the human atrium vagal stimulation and beta stimulation are synergistic and beta stimulation predominates over vagal stimulation, with direct vagal stimulation having a minimal effect.